Faktor-Faktor Penentu Efisiensi Operasional Perbankan di Indonesia - Henny Setyo Lestari; Hartini Hartini; Wafi Suryo Laksono; M. Hussin Abdullah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the factors that affect the operating efficiency of banking in Indonesia. This study uses the Pane Datal method. The data used during the period 2019-2023 were obtained from the Indonesia Stock Exchange. The dependent variable used in this study is operating efficiency. While the independent variables are credit risk, return on assets, return on equity, equity to asset ratio, deposit to liability ratio, total expense ratio, bank size, equity to liability ratio and ratio of loans loss provisions to net interest income. The results of this study indicate that return on assets has a positive effect on operating efficiency, while return on equity and loans loss provisions to net interest income have a negative effect on operating efficiency of banking in Indonesia and the credit risk ratio, equity to asset ratio, deposit to liability ratio, total expense ratio, bank size and equity to liability ratio do not affect operating efficiency of banking in Indonesia. It is hoped that the results of this study can be used by investors to determine the factors of operating efficiency of banking in Indonesia.